(untitled) (Indian Journal of Public Health Research & Development, 2021)
A quasi experimental study was conducted using one group pre test and post test research design. Convenient sampling technique was used to select 50 mothers of under five children at Bagavati village, of Bagalkot Dist, Karnataka. Data was collected using structured knowledge questionnaire. Result: The results reveal that the overall mean score was 30% in the pre test and 65.5% in the post test. Majority of the mothers had inadequate knowledge in pre test. After the implementation of Information Booklet with an enhancement of 33.5% mothers of under five children had more adequate knowledge regarding Vaccine Preventable Diseases. Paired ‘t’ test showed that there was a significant improvement between pre test and post test scores with ‘t’ value of 11.03 at P<0.05. Conclusion: The study findings revealed that information booklet on vaccine preventable diseases is effective an improving knowledge of mothers of under five children.